Analisis Metode-Metode Pembelajaran PAI di Madrasah Ibtidaiyah - Amiruddin, Ibnu; Fitriadi, Alif Bagus (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This research explains the PAI learning method in Madrasah Ibtidaiyah which has a significant role in the goal of achieving the learning process. Therefore, the method becomes a tool for an educator in carrying out the teaching and learning process professionally, teachers need sufficient and complete insight into teaching activities. One of the insights that teachers have is strategies and methods in teaching and learning. Thus an educator needs to have skills in choosing the right methods, models, strategies and approaches according to the characteristics of the subject and learners. These methods, models, strategies and approaches will only get optimal results if they can be used to achieve the goals that have been set. To achieve various learning objectives, one of the things that needs to be considered and applied is to consistently use learning models, strategies and approaches that are in accordance with the conditions in schools and madrasahs. This research is in the form of a literature study, namely research with material sources from libraries. So that what was done in making this study was an exploration of some data.